First report of a Chinese strain of coxsackie B3 virus infection in a newborn in Germany in 2011: a case report - Ronellenfitsch, Sebastian Helmut; Tabatabai, Julia; Böttcher, Sindy; Diedrich, Sabine; Frommhold, David; Schubert-Bast, Susanne; Pöschl, Johannes; Schnitzler, Paul (Journal of medical case reports, 2014)
Enteroviruses commonly encounter babies and children and infections present in a wide variety of symptoms ranging from asymptomatic infection, benign illness, and aseptic meningitis, hand-foot-and-mouth disease to severe life-threatening disease. Some newborns develop severe disease in the first 2 weeks of life and long-term sequelae may occur among survivors.